Effect on quality of paneer using unripe mango powder as a natural coagulant - Mallik, Jarita Mahadeb; Ajay J. Gokhale (Indian Journal of Dairy Science, 2024)
Paneer, an important traditional dairy product is manufactured by different types of coagulants, however, use of natural coagulants reported are few. In this study, unripe mango powder was used as the natural coagulant in paneer manufacturing. Three variables employed were unripe mango powder (12-16 g/kg), coagulation temperature (70 to 85 °C), and fat content of milk (2.00 to 4.50 %); These variables were studied using Face-centered central composite design in design expert 13.0.5.0. The proximate compositional analysis of the optimized paneer revealed 59.55 ± 0.16 % moisture, 14.68 ± 0.03 % fat, protein content 18.94 ± 0.06 %, total carbohydrate content 4.76 ± 0.23 %, ash content 2.07 ± 0.04 % and fiber content 0.5 %. The physicochemical properties studied include titratable acidity 0.43 ± 0.02 % LA., pH 6.0 ± 0.01, water activity 0.98 ± 0.01 and FFA (Free Fatty Acids) 0.16 ± 0.03 %. In the rheological characteristics of the developed paneer,values for hardness 7.29 ± 0.60N, springiness 5.83 ± 0.15mm, cohesiveness 0.31 ± 0.01, chewiness of 13.23 ± 1.57Nmm, gumminess of 2.27 ± 0.22N, and adhesiveness of 0.03 ± 0.01Nmm. Fresh paneer sample had APC (Aerobic Plate Count) of 4.72 ± 0.47 log10 cfu/g, while Yeast and Mold count and Coliform count were absent/g. The sensory scores for the optimized paneer were 43.80 ± 0.51 for flavour (out of 50), 30.15 ±0.77 for body and texture (out of 35), 8.16 ± 0.11 for colour and appearance (out of 10), and 87.11 ± 1.20 for the total score (out of 100). The yield of the optimized paneer obtained was 17 %.